Assessing Durability of Roller Compacted Concrete - Saad Issa Sarsam; Abeer Abdulqader Salih; Sura Dheyaa Tawfee (Journal of Engineering, 2023)
Roller Compacted Concrete (RCC) is a technology characterized mainly by the use of rollers for compaction; this technology achieves significant time and cost savings in the construction of dams and roads. The primary scope of this research is to study the durability and performance of roller compacted concrete that was constructed in the laboratory using roller compactor manufactured in local market. A total of (60) slab specimen of (38×38×10) cm was constructed using the roller device, cured for 28 days, then 180 sawed cubes and 180 beams are obtained from RCC slab. Then, the specimens are subjected to 60 cycles of freezing and thawing, sulfate attack test and wetting and drying. The degree of effect of the type of coarse aggregate (crushed and rounded), cement type (OPC and SRPC) and cement content on the durability of RCC were investigated. The results indicated that RCC that contain SRPC has beneficial effects on properties of RCC as compared to RCC that contain OPC after durability testing. Based on the testing results, it was concluded that the resistance of RCC specimens to freezing and thawing, wetting and drying and sulfate attack test increase as cement content increase. The results also indicate that using RCC that contain crushed aggregate has a positive effect on the overall properties of RCC, as compared with RCC that contain rounded aggregate after durability testing.